Amelioration of genetic diversity and its assessment in Brassica napus - carinata introgression lines. (October 2019) - Dhaliwal, I; Mason, A; Banga, S; Bharti, S; Banga, S S
Abstract: One of the breeding goals in Brassica napus has been to facilitate introgression of novel traits from wild or closely related species through inter- and intra-specific crosses. The present study is based on the evaluation of B. napus – carinata introgression lines (ILs) for introgressed morphological and genetic diversity in comparison to the parental B. napus lines. A set of 81 Brassica napus – carinata ILs, developed previously following a back cross strategy, was assessed for introgressed genetic diversity by comparing them with the 15 B. napus recipient parents under two environments (E1: timely sown and E2: late sown) for phenotypic expression of 13 morpho-physiological traits. Trait averages as well as trait variations were generally higher for ILs, indicating introgression of variability in the desired direction. In comparison to the parents, the ILs were observed to be early to flower, early to mature, higher yielding, had more siliquae on the main axis and the siliquae were longer. ANOVA revealed highly significant differences amongst genotypes for 10 traits of which 4 traits, viz., days to 50% flowering, days to 100% flowering, plant height and pod length were highly significant in both the environments. SNP-based chromosome-wise gene diversity, as estimated using software SELECTIONTOOL, indicated high estimates for individual chromosomes in ILs as compared to the parental lines. The phenotypic variability estimated for majority of the traits in ILs is being utilized for developing new high yielding rapeseed varieties.